2018
DOI: 10.1016/j.heares.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrophysiological and behavioural measures of electrode discrimination in adult cochlear implant users

Abstract: The plasticity of the auditory system enables it to adjust to electrical stimulation from cochlear implants (CI). Whilst speech perception may develop for many years after implant activation, very little is known about the changes in auditory processing that underpin these improvements. Such an understanding could help guide interventions that improve hearing performance. In this longitudinal study, we examine how electrode discrimination ability changes over time in newly implanted adult CI users. Electrode d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
4
18
0
Order By: Relevance
“…This reference electrode was selected to allow direct comparisons with the associated research article [3] where a contralateral electrode, relative to the CI, was used as the reference. In that study, as well as previous ones [4] , [5] , we have found that contralateral electrodes show significantly less artefacts than electrodes in close proximity to the CI. Therefore, using a contralateral reference minimized the spread of electrical artefacts offering an advantage for real-time assessment, since it is often sufficient to unveil artefact-free responses on contralateral frontal electrodes.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…This reference electrode was selected to allow direct comparisons with the associated research article [3] where a contralateral electrode, relative to the CI, was used as the reference. In that study, as well as previous ones [4] , [5] , we have found that contralateral electrodes show significantly less artefacts than electrodes in close proximity to the CI. Therefore, using a contralateral reference minimized the spread of electrical artefacts offering an advantage for real-time assessment, since it is often sufficient to unveil artefact-free responses on contralateral frontal electrodes.…”
Section: Methodssupporting
confidence: 83%
“…Therefore, using a contralateral reference minimized the spread of electrical artefacts offering an advantage for real-time assessment, since it is often sufficient to unveil artefact-free responses on contralateral frontal electrodes. Note that the use of a contralateral electrode as the reference has no impact on the quality of the responses investigated in this or previous studies [3] , [4] , [5] .…”
Section: Methodsmentioning
confidence: 68%
“…Although most subjects reported that they heard the modulation during the experiment, it is not clear what triggered the eACC. Nevertheless, Mathew et al 35,36 successfully used the eACC to assess electrode www.nature.com/scientificreports/ discrimination, and as long as the alteration made between two alternating stimuli cannot be attributed to confounding factors, this can be a clinically relevant measure which is little troubled by the stimulation artifacts. The electrophysiological measures used in the present study originate from regions in the auditory pathway beyond the periphery 17,38 and are assumed to reflect the processing cascade of all neural ensembles involved in TEM encoding of the ascending auditory pathway up to generator of the neural response.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cortical origin of the ACC it can potentially function as a final detector of how well the TEMs are encoded in the neural signal. The ACC has been successfully used as an electrophysiological measure of gap detection 33 , frequency change detection 34 , and the eACC for electrode discrimination [35][36][37] in CI users. Furthermore, the eACC N1 amplitude shows a similar pattern as the temporal modulation transfer function of CI users 38 .…”
mentioning
confidence: 99%
“…Further complications arise from the use of anaesthesia in the physiological studies (Chung et al, 2016) and from the use of different outcome measures, such as behavioural judgements in humans and single-unit recordings in animals. Recently researchers have begun to bridge this gap by combining physiological experiments with threshold and supra-threshold behavioural measures in animals (Kadner and Scheich, 2000;Vollmer et al, 2001;Pfingst et al, 2011;Benovitski et al, 2014;King et al, 2016;Rosskothen-Kuhl et al, 2021), and by developing electrophysiological measures of stimulus discrimination in humans that may in principle be applied to animal studies (Mathew et al, 2017;Mathew et al, 2018;Presacco and Middlebrooks, 2018).…”
mentioning
confidence: 99%